Evaluation of process capability index based on exponential progressively Type-Ⅱ data with effect from multiple production lines (Statistics, Optimization & Information Computing, 2025)
Process capability indices have been widely used to assess process performance to drive continuous improvement in quality and productivity, with larger ones being better for life cycle performance indicators. For multiple production lines, an overall process capability index is proposed in this paper. When the lifetime of units follows an exponential distribution and the differences in testing facilities are taken into account, the maximum likelihood estimation, uniformly minimum variance unbiased estimation and generalized estimation for the lifetime performance index were investigated. In order to investigate the advantages of each method, extensive Monte Carlo simulations are carried out. Finally, the practical applications of the proposed methods are demonstrated through the analysis of two real-life datasets.